2003
DOI: 10.1016/s0002-9440(10)63582-1
|View full text |Cite
|
Sign up to set email alerts
|

Interference with Transforming Growth Factor-β/ Smad3 Signaling Results in Accelerated Healing of Wounds in Previously Irradiated Skin

Abstract: Transforming growth factor (TGF)-beta regulates many aspects of wound repair including inflammation, chemotaxis, and deposition of extracellular matrix. We previously showed that epithelialization of incisional wounds is accelerated in mice null for Smad3, a key cytoplasmic mediator of TGF-beta signaling. Here, we investigated the effects of loss of Smad3 on healing of wounds in skin previously exposed to ionizing radiation, in which scarring fibrosis complicates healing. Cutaneous wounds made in Smad3-null mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 43 publications
12
127
1
Order By: Relevance
“…This procedure can be associated with less edema and fibrosis. Conversely, higher rates of wound healing complications have been reported when irradiation is delivered before surgery (15,16). In this experimental research, the longer delay in wound healing observed from the specimens in IG2 can be explained on the basis of Wang et al (8) and Qu et al (13,14) findings.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This procedure can be associated with less edema and fibrosis. Conversely, higher rates of wound healing complications have been reported when irradiation is delivered before surgery (15,16). In this experimental research, the longer delay in wound healing observed from the specimens in IG2 can be explained on the basis of Wang et al (8) and Qu et al (13,14) findings.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, the main components of the extracellular matrix, GAGs and collagen fibers, are synthesized by fibroblasts (7,10,11,13,14). Wound healing can be considered complete when, after reaching maturation, the newly formed collagen reestablishes the integrity of the damaged tissue (11,16). Since fibroblasts originate from cells of the surrounding undamaged connective tissue and the irradiated area comprised only an approximately 1-cm-wide zone around the wounds, it would be reasonable to assume that the observed delay in tissue repair can be attributed to direct damages in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cutaneous wounding, the number of myofibroblasts was less in Smad3 knockout mice compared to wildtype mice. However, treatment of primary neonatal dermal fibroblasts from Smad3 knockout mice with 5 ng/ml TGF-β1 for 4 days induced α-SMA protein at the same level as fibroblasts from wild-type mice [Flanders et al, 2003]. Furthermore, lung fibroblasts transfected with Smad2, but not Smad3 had up-regulated α-SMA mRNA expression and altered cell phenotypes [Evans et al, 2003].…”
Section: Discussionmentioning
confidence: 93%
“…51,52 Expression of a-smooth muscle actin (aSMA), important in fibroblast-myofibroblast conversion, is mediated by Smad2. [53][54][55] However, expression of Snail, the master transcription factor involved in the earlier step of the epithelialmesenchymal transition (EMT), as an important step in the process of tissue fibrosis in the eye, is controlled by Smad3. 56 The expression of the majority of the extracellular matrix components and enzymes involved in matrix reorganization/ maturation depends on Smad3, whereas expression of matrix metalloproteinase-2 is Smad2 dependent.…”
Section: Tgfb Signal Transduction and Tissue Fibrosismentioning
confidence: 99%